Forced-Air Convection Versus Underbody Conduction Warming Strategies to Maintain Perioperative Normothermia in Patients Undergoing Total Joint Arthroplasty - McClain, Robert (Cureus, 2020)
Background Forced-air warming is an established strategy for maintaining perioperative normothermia. However, this warming strategy can potentially contaminate the surgical field by circulating nonsterile air. This study aimed to determine whether changing practice away from this method resulted in non-inferior rates of perioperative hypothermia. Methods We performed a chart review of primary total hip and knee arthroplasty patients from 2014 to 2017, when the strategy of intraoperative forced-air warming (FAW) was changed to preoperative FAW along with intraoperative underbody conduction warming (CW) with an underbody warming mattress. Data included patient temperatures throughout all phases of care, blood loss and transfusion requirements, length of postanesthesia care unit (PACU) and hospital stays, and 30-day infection and mortality. Results A total of 769 charts were reviewed; 349 patients underwent surgery before the practice change and 420 after. Mean (SD; 95% CI) body temperatures at the time of incision were lower for group 1 than for group 2 (34.55 vs 35.52 °C [0.97 °C; 95% CI, 0.72-1.23 °C]). The average nadir of intraoperative body temperature was lower for group 1 than for group 2 (difference of means, 0.44 °C; 95% CI, 0.18-0.71 °C). Group 2 had a higher percentage of patients who presented hypothermic (temperature <36.0 °C) on arrival in the PACU (12.9% vs 7.7%). Conclusion Preoperative convective warming combined with intraoperative underbody conductive warming maintains normothermia during primary total joint arthroplasty and is non-inferior to forced-air intraoperative warming alone.